Determinan Penggunaan E-Money dengan Pendekatan Model UTAUT 2 dan Risiko yang Dirasakan - Nurabiah, Nurabiah; Pusparini, Herlina; Fitriyah, Nur (E-Jurnal Akuntansi; Vol 33 No 1 (2023), 2023)
The research objective is to analyze what factors influence the use of e-money with the extended unified theory of acceptance and use of technology (UTAUT2) theoretical approach. Data collection using a questionnaire. The research sample was e-money users aged 17-35 years as a proxy for the millennial generation in Mataram City with a total of 287 respondents. The results of empirical data testing show that the behavioral intention variable has a significant positive effect on use behavior, the habit and perceived risk variables have a significant effect on behavioral intention, the perceived risk variable has a significant positive effect on financial risk, performance risk, and privacy risk and habit has a significant effect on use behavior. Meanwhile, the variable effort expectancy, facilitating conditions, hedonic motivation, performance expectancy, price value, and social influence do not affect behavioral intention and facilitating conditions do not affect use behavior. Keywords: Determinant; E-Money ; Risk; UTAUT 2